Implementação e Avaliação de um Mecanismo de Escambo para Promover Reciprocidade em Federações de Provedores de Computação na Nuvem - Falcão, Eduardo de Lucena; Brasileiro, Francisco; Brito, Andrey; Germano, Francisco (Anais do Workshop em Clouds e Aplicações (WCGA); 2018: Anais do XVI Workshop em Clouds e Aplicações, 2018)
A big challenge when designing and operating a federation of cloud computing providers is the implementation of a suitable business model that enables the federation to function appropriately. Barter-based business models were proposed as a cheap and efficient way to mediate transactions between the providers that form the federation. In this work, we discuss the challenges related to the implementation of a barter mechanism in a federation of cloud computing providers, proposed by us previously. The performance of the mechanism is evaluated through controlled experiments. The results obtained corroborate previous results obtained with simplified simulation models. In particular, the mechanism in place is able to ensure fairness in the use of resources while maintaining the satisfaction of collaborative members at sufficiently high levels.